The Effect of Village Original Income, Village Fund, Village Allocation Fund, and APBD Financial Assistance on Village Expenditure in the Field of Village Development (A Study of Suka Makmur Village, Binjai Subdistrict, Langkat Regency) - Meliana, Meliana; Mardhiyah, Najla Ainal; Nainggolan, Benny Rojeston Marnaek; Situmorang, Dokman Marulitua (Lembaga Riset Ilmiah, 2025)
This study analyzes the effect of village revenue sources on development expenditure in Suka Makmur Village, Langkat Regency. Using financial data from 2020-2024 across six hamlets (60 observations), the research applies multiple linear regression with classical assumption testing. The results show that Village Original Income (PADes) does not have a significant effect (sig. 0.758), while Village Fund (DD) (sig. 0.047), Village Allocation Fund (ADD) (sig. 0.037), and APBD Financial Assistance (sig. 0.029) have a positive effect. Overall, these variables explain 76.8% of the variation in development expenditure (R²=0.768). The findings reveal a high dependence on external funds, with PADes still not fully optimized. The implication is that there is a need to improve internal fiscal capacity through the optimization of local potential, while maintaining accountability in the management of transfer funds. The study recommends intensive assistance to strengthen fiscal independence at the village level and further research on non-financial factors supporting development.